Antilope, A Portable Low-Cost Sensor System for the Assessment of Indoor and Outdoor Air Pollution Exposure - Lenartz, Fabian; Dury, Marie; Bergmans, Benjamin; Hutsemékers, Virginie; Broun, Valéry; Brose, Christophe; Guichaux, Sylvain (Frontiers in Sensors, 2021)
The increasing availability of low-cost sensors and open source projects make it easier than ever for a maker to build his own air quality node. Nonetheless, depending on one’s goal and its related data quality objective, to customize an existing project or to build a specific printed circuit board may still be very useful. In the framework of the Outdoor and Indoor Exposure project, a portable mini-station has been developed, tested and then used in two experiments: exposure assessment and complementary network measurement. The present paper focuses on the description of the equipment that was designed and prototyped, as well as on the tests that were made in the lab and in the field to evaluate its overall performance and that of its different sensors. Finally, we present what we consider to be its main drawbacks and our perspectives for further development and tests.